The prevalence of stillbirth due to antenatal complications (hypertension, diabetes, and anemia): a single center study in Malaysia / Nur Syamimi Haji Abu Bakar ... [et al.] - Abu Bakar, Nur Syamimi; Awang, Nur ‘Ainina; Amin Burhanuddin, Siti Nur Zahrah; Ismail, Adriana; Mat Rani, Ruzanita; Ali, Anita Rina; Wan Hassan, Wan Hamilton; Alias, Nur Aqilah (Faculty of Health Sciences, Universiti Teknologi MARA, 2023)
Stillbirth is a serious problem globally with approximately 2.65 million third trimester stillborn baby cases recorded around the world each year. In Malaysia, there are very limited studies on the risks of stillbirth. Thus, the objective of the study was to investigate the odds and probability of stillbirth due to antenatal complications (hypertension, diabetes and anemia) among women in Malaysia. A case-control study was undertaken at Hospital Serdang in Selangor. The sample size for the study is 367 patients who gave birth at this hospital of which 155 are stillbirths (cases) and 212 are the alive (controls). The data was collected from 2013 to 2015 based on the patient’s data in the manual book and database. A descriptive analysis is conducted to know the percentage of mothers with antenatal problems with the birth of their babies. A chi-square test of independence was conducted to identify the association between antenatal complications and stillbirth. The binary logistic regression (odd ratio) is implemented to identify the risk factors of antenatal complications toward stillbirth. The results showed that most of the stillborn baby’s mothers did not have any antenatal complications during pregnancy just 18.1% had hypertension, 18.7% had diabetes and 23.2% had anemia. Mothers with babies born alive showed quite similar results with only 18.9% having diabetes and 25% having anemia but a slight difference in hypertension with only 1.9%. The chi square tests of independence results concluded that only hypertension is associated with the birth of a baby. Based on the odds ratio, a mother who has hypertension during pregnancy has 11.465 times higher odds (95 CI: 3.930 to 33.445) of getting a stillborn baby compared to a mother without hypertension. Thus, pregnant women who have hypertension during pregnancy have a higher risk of having a stillborn baby. So, if hypertension is detected during pregnancy, the doctor and mother should be more careful and always monitor the progress of the baby to avoid a stillbirth.